Structure and mechanism of a canonical poly(ADP-ribose) glycohydrolase. - Dunstan, MS; Barkauskaite, E; Lafite, P; Knezevic, C; Brassington, A; Ahel, M; Hergenrother, P; Leys, D; Ahel, I (2012)
Poly(ADP-ribosyl)ation is a reversible post-translational protein modification involved in the regulation of a number of cellular processes including DNA repair, chromatin structure, mitosis, transcription, checkpoint activation, apoptosis and asexual development. The reversion of poly(ADP-ribosyl)ation is catalysed by poly(ADP-ribose) (PAR) glycohydrolase (PARG), which specifically targets the unique PAR (1''-2') ribose-ribose bonds. Here we report the structure and mechanism of the first canonical PARG from the protozoan Tetrahymena thermophila. In addition, we reveal the structure of T. thermophila PARG in a complex with a novel rhodanine-containing mammalian PARG inhibitor RBPI-3. Our data demonstrate that the protozoan PARG represents a good model for human PARG and is therefore likely to prove useful in guiding structure-based discovery of new classes of PARG inhibitors.